2014
DOI: 10.3109/07420528.2014.925470
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype, gender, and time for sex

Abstract: preference was more strongly related to the timing of need for sex than to the timing of actual sexual activity (r = -.275 vs. r = -.174), while the timing of desire and the timing of sexual activity were positively, but moderately related (r = .320).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…Jankowski et al (2014) have shown that there is a general major evening peak of sexual activity and desire in females, regardless of their chronotype. Whereas in males, the greatest need for sex occurred either in the morning or evening hours according to their chronotype (evening types at 9:00–12:00 and 18:00–3:00 and in morning types at 6:00–12:00 and 18:00–24:00).…”
Section: Methodsmentioning
confidence: 99%
“…Jankowski et al (2014) have shown that there is a general major evening peak of sexual activity and desire in females, regardless of their chronotype. Whereas in males, the greatest need for sex occurred either in the morning or evening hours according to their chronotype (evening types at 9:00–12:00 and 18:00–3:00 and in morning types at 6:00–12:00 and 18:00–24:00).…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps because significant correlations have been found between morningness-eveningness and several psychological traits [10][11][12][13][14], the classification of chronotypes has attracted great attention from social scientists. As of February 2016, Horne and Östberg's original publication was the article with the highest number of citations of any article retrieved by the keyword "circadian" in the Web of Science database (produced by Thomson Reuters, New York, NY).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the majority of sexual encounters take place at bedtime, that is, people begin to sleep after having sex, while some of the encounters do occur during the daytime [45]. However, approximately 20% of sexual encounters take place early in the morning [46]. It is reasonable to assume that REM sleep-related erections have a function of recreation, such as resolving marital conflict.…”
Section: Sexual Intercourse With Nptmentioning
confidence: 99%